Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1002/pssa.2211080145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high pressure on cathodoluminescence of cubic boron nitride

Abstract: It is shown that the pressure treatment of boron nitride (BNsph) polycrystals a t room temperature results in the change of broad band parameters (A, B, C) and zero-phonon lines of cathodoluminescent (CL) spectra, and in the appearance of RC centers. In the pressure treated ceramic samples BNsph the PC-1 (2.84 eV), PC-2 (2.325 eV), PC-3 (1.79 eV) centers of presumably interstitial nature are found. The comparative analysis of the dependence of the broad bands parameters and zero-phonon lines of the GC centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Compared with the previous works, the emission band at about 2.48 eV was considered to be the A and B bands that are caused by multivacancy complexes of boron and nitrogen vacancies in cBN single crystals. 5 In our films, the existence of boron and nitrogen vacancies were indeed demonstrated by the elemental fluctuation in the in-depth secondary ion mass spectroscopy measurements. 14 The main broad peak at about 3.12 eV closes to the band UCL ͑or US-1͒ luminescence centers reported previously.…”
Section: Cathodoluminescence Of Cubic Boron Nitride Films Deposited Bsupporting
confidence: 54%
See 1 more Smart Citation
“…Compared with the previous works, the emission band at about 2.48 eV was considered to be the A and B bands that are caused by multivacancy complexes of boron and nitrogen vacancies in cBN single crystals. 5 In our films, the existence of boron and nitrogen vacancies were indeed demonstrated by the elemental fluctuation in the in-depth secondary ion mass spectroscopy measurements. 14 The main broad peak at about 3.12 eV closes to the band UCL ͑or US-1͒ luminescence centers reported previously.…”
Section: Cathodoluminescence Of Cubic Boron Nitride Films Deposited Bsupporting
confidence: 54%
“…However, few research works on the luminescence properties have been reported, and these works were performed mainly on the cBN crystals synthesized by high-temperature, high-pressure ͑HTHP͒ method. [2][3][4][5][6][7][8] Up to now, about 20 luminescence centers have been observed, but the origin of these luminescence centers has not been identified. For the cBN films deposited by physical or chemical vapor deposition, there has been only one work by Taylor et al, 9 which studied the deep-level emission spectra of nanocrystalline cBN films deposited by rf magnetron sputtering deposition.…”
Section: Cathodoluminescence Of Cubic Boron Nitride Films Deposited Bmentioning
confidence: 99%
“…Commercial hexagonal BN powder was used. Small single crystals of cubic BN were sintered at Institute of Solid State and Semiconductor Physics, National Academy of Belarus [7]. The experimental apparatus described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Studying the excitation thresholds of the photoluminescence bands and correlating with expectations of band gaps can help in distinguishing h-BN, BN-nt, and impurity contributions to the spectra. In view of previous studies in the Riga laboratory of cubic-BN ceramic [6], and the fact that cubic-BN is the other structural paradigm in this intended study, single crystal samples [7] of c-BN have been included.…”
Section: Introductionmentioning
confidence: 99%
“…The O N −V B center also shares much of the characteristics of the GC-2 center often observed in c-BN. [9][10][11][12][13] Experimentally, optical properties of defects in c-BN have been investigated using photoluminescence (PL) and cathodoluminescence (CL) techniques. [9][10][11][12][13][14][15] Identification of defect center in c-BN using electron spin resonance (ESR) experiments have also been reported.…”
mentioning
confidence: 99%